2018
DOI: 10.1002/psc.3131
|View full text |Cite
|
Sign up to set email alerts
|

Development of lipopolyplexes for gene delivery: A comparison of the effects of differing modes of targeting peptide display on the structure and transfection activities of lipopolyplexes

Abstract: The design, synthesis and formulation of non‐viral gene delivery vectors is an area of renewed research interest. Amongst the most efficient non‐viral gene delivery systems are lipopolyplexes, in which cationic peptides are co‐formulated with plasmid DNA and lipids. One advantage of lipopolyplex vectors is that they have the potential to be targeted to specific cell types by attaching peptide targeting ligands on the surface, thus increasing both the transfection efficiency and selectivity for disease targets … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 54 publications
0
15
0
Order By: Relevance
“…Indeed, we have previously demonstrated that lipopolyplexes formulated with P1 effectively deliver pDNA encoding for a biosensor to HCC1954 and MDA-MB-231 breast cancer cell lines in vivo , 30 and that lipopolyplexes formulated with P1 , P2 or P3 effectively transfect HCC1954 cells in vitro . 49 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, we have previously demonstrated that lipopolyplexes formulated with P1 effectively deliver pDNA encoding for a biosensor to HCC1954 and MDA-MB-231 breast cancer cell lines in vivo , 30 and that lipopolyplexes formulated with P1 , P2 or P3 effectively transfect HCC1954 cells in vitro . 49 …”
Section: Resultsmentioning
confidence: 99%
“…General methods for chemical synthesis and solid phase peptide synthesis, sources of chemicals, purification and analytical methods are in the ESI. † Peptides P1 , 49 P2 , 49 P3 , 49 P4 , 30 and P6 30 were synthesized according to the published literature procedures. Experimental procedures for the synthesis of 3 , 8 , 10 , S6 , P5 and 7 ; HPLC/HRMS for peptides 1 , 17 , P5 , 7 and 1 H/ 13 C NMR spectra for novel compounds can be found in the ESI.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CA structure significantly affects the efficiency of NA delivery to eukaryotic cells. In recent years, many monocationic amphiphiles have been obtained [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ] that form liposomes for NA delivery. In this review, we will consider polycationic amphiphiles, which, compared to monocationic analogs, enable the more efficient transport of NAs into cells due to the formation of a system of distributed charges in the polyamine matrix and their ability to facilitate NA release from endosomes.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the vehicles called “lipopolyplexes” reported in the current literature have this basic structure [ 3 , 4 , 5 , 6 ]. This design allows the generation of particles that present similarities with a viral particle, especially their small size and organization.…”
Section: Introductionmentioning
confidence: 99%